2019
DOI: 10.1080/01443410.2019.1645306
|View full text |Cite
|
Sign up to set email alerts
|

Inspecting a picture before reading affects attentional processing but not comprehension

Abstract: This study investigated whether presenting a picture before reading can encourage situation-model construction. We compared two conditions (n ¼ 30) which differed in whether a picture of the initial situation described in a narrative text was presented before reading (i.e. pictorial-support condition) or not (i.e. no-picture condition). Situation-model construction was measured using both process-and product-oriented measures. Eye-tracking data indicated online resource allocation to the different levels of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The authors reported that the eye-movement patterns of the participants who visualized the supporting picture reflected increased effort in processing information to generate inferences, whereas those who did not visualize the picture were more focused on processing literal information. Although there were no differences in text comprehension outcomes between both conditions (for tentative explanations see Wassenburg et al, 2020), this result indicates that visualizing a supporting image shapes subsequent reading behaviour.…”
Section: Visual Support For Adultsmentioning
confidence: 64%
See 4 more Smart Citations
“…The authors reported that the eye-movement patterns of the participants who visualized the supporting picture reflected increased effort in processing information to generate inferences, whereas those who did not visualize the picture were more focused on processing literal information. Although there were no differences in text comprehension outcomes between both conditions (for tentative explanations see Wassenburg et al, 2020), this result indicates that visualizing a supporting image shapes subsequent reading behaviour.…”
Section: Visual Support For Adultsmentioning
confidence: 64%
“…To fill this gap, Eitel and Scheiter called for increasing research analysing readers' eye movements during the reading course. Two exceptions to the lack of this type of research are the studies by Ferreira et al (2013) and, more recently, by Wassenburg et al (2020). Ferreira et al (2013) established that a preview of objects is critical to the observance of garden-path effects in the visual world paradigm.…”
Section: Visual Support For Adultsmentioning
confidence: 99%
See 3 more Smart Citations